The influence of gratitude and personality traits on career resilience and career success among college students - Zhao, Kai; Ji, Wenna (Frontiers in Psychology, 2024)
The study examines the interplay between gratitude and career success, with career resilience as the mediating mechanism and personality traits, i.e., conscientiousness and extraversion, as moderating factors. The overarching goal is to enhance our understanding of the complex dynamics that influence career outcomes of college students in China. Data are gathered through a survey-based technique, capturing responses from a diverse sample of participants. The analysis employs Structural Equation Modeling (SEM) to explore the relationships among gratitude, career resilience, personality traits, and career success. The results reveal that gratitude impacts students' career success through the mediating mechanism of career resilience. In addition, conscientiousness and extraversion are found to positively intervene the direct effect between gratitude and career resilience and the indirect effect between gratitude and career success through career resilience. The findings offer valuable insights for individuals, organizations, and career development practitioners, emphasizing the importance of cultivating gratitude and recognizing the differential impact of personality traits on this process. As organizations seek to foster resilient and successful career paths, acknowledging these nuanced dynamics can inform targeted interventions and strategies.